Automatic slice thickness measurement on computed tomography images of American College of Radiology phantom - Anam, Choirul; Insiano, Dewi A.; Hidayanto, Eko; Naufal, Ariij; Maya, Annisa Tenri; Mulatomo, Tunggul Drajat; Ali, Mohd Hanafi (Institute of Advanced Engineering and Science, 2024)
This study aims to develop an automatic method for calculating slice thickness on an American College of Radiology (ACR) phantom and evaluate its accuracy at variations of orientation angle and slice thickness. The phantom was scanned using Siemens SOMATOM perspective, with variations of the slice thickness (i.e. 1.5, 3, 5, 6, 7, and 10 mm) and rotation angles (i.e. 0.0, 22.5, 45.0, and 67.5°). The phantom rotation was based on the bone object as a reference. After determining the rotation angle, the phantom image was rotated by the angle. Next, profiles of pixel values across the wire objects for measuring slice thickness were developed from rotated phantom images. The slice thickness was measured automatically from the obtained profiles. The results of the automated method are 2.5, 4.1, 5.4, 5.8, 7.8, and 9.8 mm for all varied slice thicknesses. The differences between the automatic and manual methods are within 0.3 mm. The automatic method is capable of detecting slice thickness for various angles. The differences in slice thickness for various angles are within 0.1 mm for a slice thickness of 3 mm. These results are similar when compared to manual measurements. An algorithm for automated slice thickness measurement on ACR phantom has been successfully developed.